Revitalisasi Nilai-Nilai Kearifan Lokal dalam Civic Culture: Studi Kasus Tradisi Tolak Bala di Kabupaten Buol - Triadityansyah, Moh; Kamuli, Sukarman; Djaafar, Lucyane (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Globalization often brings social changes that lead to a decline in community participation in preserving local wisdom. This study aims to analyze the revitalization process of the Tolak Bala tradition and its contribution to strengthening civic culture, particularly in cultural preservation and identity reinforcement. This research employs a descriptive qualitative method to illustrate social phenomena in their actual context and to uncover the characteristics and meanings of these realities. Data collection was conducted through observations, interviews, and documentation, with informants including traditional leaders, community figures, and residents from two villages in Buol Regency. Data analysis techniques involved data reduction, data presentation, and conclusion drawing. The findings indicate that strengthening civic culture through the Tolak Bala tradition is associated with several key values: cultural values that reinforce local identity, social values that enhance solidarity among residents, religious values that serve as a means of seeking divine protection, and intellectual values that encourage critical reflection on human relationships with nature and spiritual entities. The revitalization of this tradition has been carried out through several initiatives, including (1) cultural education and outreach, (2) the development of cultural festivals, (3) support from the government and relevant institutions, (4) involvement of younger generations, and (5) the use of social media to expand the reach of information and cultural promotion. This study is limited to the context of Buol Regency, so its findings may not be generalizable to other regions with different social characteristics and traditions. Further research is needed to explore the effectiveness of this revitalization process in a broader context.